Kearifan Universal dalam Perspektif Realisme Religius Comenius - Teguh Wibowo; Novita Rully A (Metalanguage: Jurnal Ilmu Bahasa dan Sastra Indonesia, 2022)
John Amos Comenius with his ideas around universal wisdom, knowledge and education. Comenius is known as a figure of religious realism and modern education. An intertwined pattern. Realism is a philosophical school that has a broad scope. Realism is the view that all sense objects or objects are real and exist alone, without relying on other knowledge or sense awareness. The main purpose of moral education is the salvation of souls. Children must be able to learn to keep the heart inside and stay away from sin. God will offer salvation to His creatures, and His creatures must be able to determine whether or not to accept the offer. This will lead to a habit of making the right decisions. Comenius saw education as a unifying force for mankind. He believes that universal character or education can help maintain world peace. He also linked knowledge of divinity and believing that by acquiring knowledge, mankind was ultimately directed to God. Comenius also wrote about his way of leading teaching, he wrote, "Students should not be overburdened with lessons that are not appropriate for their age, comprehension power, and circumstances at the time". Comenius' educational ideas include: education for everyone, learning is natural, learning in easy steps, learning by play, and lifelong learning.